Approach to Simplify the Development of IoT Systems that Interconnect Embedded Devices Using a Single Program - Matilla Blanco, Enol; Pascual Espada, Jordán; Gonzalez Crespo, Rubén (CMC: Computers, Materials & Continua, 2024)
Many Internet of Things (IoT) systems are based on the intercommunication among different devices and centralized systems. Nowadays, there are several commercial and research platforms available to simplify the creation of such IoT systems. However, developing these systems can often be a tedious task. To address this challenge, a proposed solution involves the implementation of a unified program or script that encompasses the entire system, including IoT devices functionality. This approach is based on an abstraction, integrating the control of the devices in a single program through a programmable object. Subsequently, the proposal processes the unified script to generate the centralized system code and a controller for each device. By adopting this approach, developers will be able to create IoT systems with significantly reduced implementation costs, surpassing current platforms by more than 10%. The results demonstrate that the single program approach can significantly accelerate the development of IoT systems relying on device communication
Keywords: IoT; interconnected devices; IoT platform; programing devices; devices coordination and communication; Scopus